2023
DOI: 10.3390/educsci13090885
|View full text |Cite
|
Sign up to set email alerts
|

AI-Supported Academic Advising: Exploring ChatGPT’s Current State and Future Potential toward Student Empowerment

Daisuke Akiba,
Michelle C. Fraboni

Abstract: Artificial intelligence (AI), once a phenomenon primarily in the world of science fiction, has evolved rapidly in recent years, steadily infiltrating into our daily lives. ChatGPT, a freely accessible AI-powered large language model designed to generate human-like text responses to users, has been utilized in several areas, such as the healthcare industry, to facilitate interactive dissemination of information and decision-making. Academic advising has been essential in promoting success among university stude… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The ease of ChatGPT use is a notable feature of this tool promoting its widespread accessibility and usability 58 . As previously illustrated in various studies, ChatGPT responds to queries in various languages, with notable capabilities facilitating the generation of coherent responses 11,30,[80][81][82] . A study among university students in Jordan by Ajlouni et al showed that a majority of participants (73%) agreed on the potential of ChatGPT in facilitating the learning process 83 .…”
Section: Discussionmentioning
confidence: 98%
“…The ease of ChatGPT use is a notable feature of this tool promoting its widespread accessibility and usability 58 . As previously illustrated in various studies, ChatGPT responds to queries in various languages, with notable capabilities facilitating the generation of coherent responses 11,30,[80][81][82] . A study among university students in Jordan by Ajlouni et al showed that a majority of participants (73%) agreed on the potential of ChatGPT in facilitating the learning process 83 .…”
Section: Discussionmentioning
confidence: 98%
“…The ease of ChatGPT use is a notable feature of this tool promoting its widespread accessibility and usability [57]. As previously illustrated in various studies, ChatGPT responds to queries in various languages, with notable capabilities facilitating the generation of coherent responses [11,33,[70][71][72]. A recent study among university students in Jordan by Ajlouni et al showed that a majority of participants (73%) agreed on the potential of ChatGPT in facilitating the learning process [73].…”
Section: Discussionmentioning
confidence: 99%
“…ChatGPT often generates reasonable responses in conversations, providing specialized solutions and guidance for tasks ranging from simple to complex (Zhu et al, 2023). For example, ChatGPT generated surprisingly high-quality answers in the area of academic advising for students, written in an authoritative tone, and especially, adept at addressing general career-related questions, such as career prospects, in a clear and comprehensive manner (Akiba and Fraboni, 2023). In the field of physics education, ChatGPT can solve some physics calculation tasks, explaining problem solutions at the human level (Liang et al, 2023).…”
Section: Supporting Idea Generation and Providing Quality Explanationsmentioning
confidence: 99%